The Routledge handbook to the culture and media of the Americas
1 online resource
Keywords: "Exploring the culture and media of the Americas, this handbook places particular emphasis on collective and intertwined experiences and focuses on the transnational or hemispheric dimensions of cultural flows and geocultural imaginaries that shape the literature, arts, media and other cultural expressions in the Americas. The Routledge Handbook to the Culture and Media of the Americas charts the pervasive, asymmetrical flows of cultural products and capital and their importance in the development of the Americas. The volume offers a comprehensive understanding of how Inter-American communication is constituted, framed and structured and covers the artistic and political dimensions that have shaped literature, art and popular culture in the region. Forty-six chapters cover a range of inter-American key concepts and dynamics, divided into two parts: Literature and Music deals with inter-American entanglements of artistic expressions in the Western Hemisphere, including music, dance, literary genres and developments. Media and Visual Cultures explores the inter-American dimension of media production in the hemisphere, including cinema and television, photography and art, journalism, radio, digital culture and issues such as freedom of expression and intellectual property"--